Food Service for Convicts in Correctional Institutions According to Laws and Regulations and Islamic Sharia - Ahyar Ahyar (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The rights of convicts as Indonesian citizens who lost their independence due to criminal acts must be carried out in accordance with human rights. One of them is the right to obtain adequate food and beverage services that meet nutritional and health standards in accordance with the provisions of laws and regulations. In addition, Islamic sharia (law) also regulates the rights of convicts to get good and halal food and drink. This requirement is an order from the Al-Quran and Hadith. The problem of this research is how to organize food according to the provisions of laws and regulations and the provisions of Islamic law. This research used sociological research method. According to the type and nature of the research, the data sources used are secondary data consisting of primary legal materials. The secondary legal materials in this research consist of books, scientific journals, papers and scientific articles that can provide explanations of the primary legal materials. The results of the research found that in practice it was still found in Correctional Institutions that the rights of convicts had not been given in accordance with their rights as citizens. This is caused by several factors, including the lack of understanding of the regulations regarding the rights of convicts contained in the Law and sharia law by correctional Institution officers or even by the convicts themselves. Correctional officers need to be given dissemination regarding their obligation to provide food for convicts in accordance with laws and regulations.